Pyruvate Oxidase as a Critical Link between Metabolism and Capsule Biosynthesis in Streptococcus pneumoniae. - Haley Echlin; Matthew W Frank; Amy Iverson; Ti-Cheng Chang; Michael D L Johnson; Charles O Rock; Jason W Rosch (PLoS Pathogens, 2016)
The pneumococcus is one of the most prodigious producers of hydrogen peroxide amongst bacterial pathogens. Hydrogen peroxide production by the pneumococcus has been implicated in antibiotic synergism, competition between other bacterial colonizers of the nasopharynx, and damage to epithelial cells. However, the role during invasive disease has been less clear with mutants defective in hydrogen peroxide production demonstrating both attenuation and heightened invasive disease capacity depending upon strain and serotype background. This work resolves these conflicting observations by demonstrating that the main hydrogen peroxide producing enzyme of the pneumococcus, SpxB, is required for capsule formation in a strain dependent manner. Capsule production by strains harboring capsules with acetylated sugars was dependent upon the presence of spxB while capsule production in serotypes lacking such linkages were not. The spxB mutant had significantly lower steady-state cellular levels of acetyl-CoA, suggesting that loss of capsule arises from dysregulation of this intermediary metabolite. This conclusion is corroborated by deletion of pdhC, which also resulted in lower steady-state acetyl-CoA levels and phenocopied the capsule expression profile of the spxB mutant. Capsule and acetyl-CoA levels were restored in the spxB and lctO (lactate oxidase) double mutant, supporting the connection between central metabolism and capsule formation. Taken together, these data show that the defect in pathogenesis in the spxB mutant is due to a metabolic imbalance that attenuates capsule formation and not to reduced hydrogen peroxide formation.